'Business model and performance in the Spanish wine industry'. (2nd January 2019) - Ferrer-Lorenzo, Juan Ramón; Maza-Rubio, María Teresa; Abella-Garcés, Silvia
ABSTRACT: Using a business model as a means of analysis of competitive advantage is a new concept that includes classic elements, such as resources and strategy, adding the creation of value for customers and the appropriation of a part of it by the company. This paper studies the relation between the business model and performance in the Spanish wine industry. For this study, a survey was conducted of all the wineries in Spain; 339 responses were obtained, 14% of the total sample universe. In line with the recent literature, a business model is shaped as a consequence of the definition of the business strategy. To analyse the different business models, the core strategy and their interaction with the decisions of the company in the value chain have been analysed. The study empirically points out four successful business models in the Spanish wine industry, and notes the set of decisions in the value chain that each business model uses. The results and conclusions presented should provide a way for the managers of Spanish wineries to evaluate the congruence between their core strategies and their decisions in the value chain in order to achieve a better business performance. In addition, this can benefit wine sector firms in aligning their resources and decisions and in achieving greater efficiency. The study provides a global analysis that has not been made in the wine sector before and its conclusions allow one to know which core strategies are related to a better performance and which are not.